2013
DOI: 10.1158/1078-0432.ccr-12-2616
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Man Phase I Study of GC33, a Novel Recombinant Humanized Antibody Against Glypican-3, in Patients with Advanced Hepatocellular Carcinoma

Abstract: Purpose: GC33 is a novel recombinant fully humanized monoclonal antibody that binds to human glypican-3 (GPC3). The antitumor activity of GC33 was shown in preclinical models of hepatocellular carcinoma (HCC). This first-in-man clinical trial was conducted to evaluate the safety, pharmacokinetic characteristics, and preliminary efficacy of GC33 in patients with advanced HCC.Experimental Design: Patients with measurable, histologically proven, advanced HCC were enrolled to a dose-escalation study of GC33 (2.5-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
131
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(140 citation statements)
references
References 28 publications
(35 reference statements)
7
131
0
1
Order By: Relevance
“…A monoclonal antibody against GPC3 showed good antitumour activity in vitro, and a phase one trial subsequently showed increased median time to progression in HCC with high GPC3 expression (26.0 weeks compared to 7.1 weeks for GPC3-low tumours). 21 A score incorporating GPC3 staining intensity and pattern showed good predictive ability in this study.…”
Section: Prediction Of Treatment Response In Hepatocellular Carcinomasupporting
confidence: 57%
“…A monoclonal antibody against GPC3 showed good antitumour activity in vitro, and a phase one trial subsequently showed increased median time to progression in HCC with high GPC3 expression (26.0 weeks compared to 7.1 weeks for GPC3-low tumours). 21 A score incorporating GPC3 staining intensity and pattern showed good predictive ability in this study.…”
Section: Prediction Of Treatment Response In Hepatocellular Carcinomasupporting
confidence: 57%
“…Moreover, the naked antibody could not completely eliminate tumors in mouse models, and no partial or complete response was observed in the 15 patients evaluated during the phase I clinical trial of GC33, suggesting that the therapeutic effects of a naked antibody may not be potent enough for curative treatment of HCC (14). In the phase I clinical trial of a GPC3-derived peptide vaccine for patients with HCC, the median overall survival seemed to positively correlate with the GPC3-specific CTL frequencies, suggesting that GPC3-targeted T cells could be potential agents for HCC treatment (12).…”
Section: Introductionmentioning
confidence: 99%
“…GC33 is a humanized monoclonal antibody against GPC3 and it mediates antibody-dependent cell cytotoxicity [72]. A Phase I study demonstrated that GC33 was well tolerated in HCC [73]. In a recent randomized Phase II trial, 185 patients that had advanced HCC and had failed prior systemic therapy were randomized to receive GC33 at 1600 mg intravenously on days 1 and 8 and then every 2 weeks afterwards, or placebo.…”
Section: Glypican 3: Challenges In Biomarker Driven Studiesmentioning
confidence: 99%